English students’ experience of reframing narrative stories from a critical literacy perspective - Gustine, Gin Gin; Insani, Hikmah Nur (Universitas Pendidikan Indonesia, 2019)
This article reports a study investigating the English teacher’s strategies for assisting secondary school students of English to be critically literate through an analysis of narrative texts. In this study, Luke and Freebody’s (1999) four resources model of critical literacy was used as a framework for English instruction situated in an Indonesian secondary school. Data were collected from classroom observations, students’ reflective journals, and an interview with secondary school students. The findings showed that the four resources model of critical literacy, to some extent, helped students to become critically literate especially at the stage of meaning-making-of and criticizing the text. The implication of the study is that there is the possibility of implementing critical literacy-oriented English classrooms in Indonesian and Asian secondary schools.